APPLE YIELD ESTIMATION ON THE BASIS OF MORPHOLOGICAL CHARACTERS: A STATISTICAL APPROACH - SHARMA, ANJU; MAHAJAN, P. K.; SATISH K. SHARMA, O. K.BELWAL AND (The Bioscan, 2018)
An attempt has been made to develop models for yield estimation of apple on the basis of morphological characters through correlation and regression techniques at three different locations of Himachal Pradesh viz., Shimla, Kotkhai and Theog. Highest correlation coefficient was obtained between number of spurs and number of flowers (0.98), followed by between age and girth (0.81) at Shimla location. Number of fruits, flowers and spurs were perfectly correlated with each other in Kotkhai and Theog regions. The use of age (exponential), girth (exponential) and spread (cubic) was found to be the best independent variables for estimating the apple yield in Shimla, Kotkhai and Theog locations respectively. Age and length of spurs had significant effect on yield estimation at Shimla location while spread of the tree and length of spurs contributed significantly to the yield of tree at Kotkhai. In Theog location, age, height, number of secondary branches and length of spurs contributed significantly to the yield estimation. The model, X12=b0 X1 b1X2 b2X3 b3X4 b4X5 b5X6 b6X7 b7X8 b8X9 b9X10 b10X11 b11 fitted best with 0.560 and 0.925 as adjusted R2 value respectively at Shimla and Kotkhai locations, while X12=b0 +b1X1 +b2X2 +b3X3 +b4X4+ b5X5+ b6X6+ b7X7+b8X8 + b9X9+b10X10 +b11 X11 was found to be best fit at Theog location with 0.956 as adjusted R2 value